Per lo studio della rivoluzione cinese. [Contri di] P. Fedosseev, R.I. Kosopalov, [e a. Trad.] (Ideologie, 1971)
Bibl., ill., index. Ideologie. Vol. IV. 1970, nn. 13-14, lugliodicembre, Fascicolo speciale.